Oxford American children's encyclopedia. [Volume] 4, gypsies-materials - Keene, Ann T. (New York : Oxford University Press, 2002)
Presents hundreds of color-illustrated, alphabetized entries on the people, places, and things that shape the world, written especially for young readers. This volume covers "Gypsies" through "Materials.".
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
3-6
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries; Encyclopedias and dictionaries